Effectiveness of Use of Audio-Visual Media for Improving 2021/2022 Kisaran High School Students' Listening Skills in Indonesian Language Education Subjects - Atikah Nasution, Wan Nurul; Mapilindo, Mapilindo; Rahmayanti, Sri (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This research is motivated by the teacher's ineffectiveness in using instructional media and is only based on the accuracy in selecting it for each lesson carried out in class. The aims of the study were, 1) To find out the listening skills of class XI students of SMA N 1 Kisaran, 2) To find out the use of audio-visual media in Indonesian language learning students, class XI SMA N 1 Kisaran 3) To find out the improvement in listening skills of students of class XI SMA N 1 Kisaran in learning Indonesian after using audio-visual media. The research approach uses qualitative methods with Classroom Action Research which consists of three cycles (Pre-Cycle, Cycle 1, Cycle 2). The instruments used were observation sheets, test questions (test and re-test), interview guidelines, and documentation studies. The sample size of the study was 35 students of class XI SMA N 1 Kisaran. The results showed an increase in the average score of the final listening test after receiving treatment on the effectiveness of the use of audiovisual media from each cycle. The results of the study were also taken from the results of the partner teacher's assessment (observer) that the research found good results from pre-cycle to cycle 2 and there was no need to continue research into the next cycle. Teacher creativity in terms of improving learning outcomes needs to be considered in every use of learning media, especially the use of audiovisual media in learning to listen to Indonesian language education subjects.